2013
DOI: 10.1037/a0031398
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of working memory in the (re-)planning and execution of grasping movements.

Abstract: Three experiments were conducted to dissociate movement planning costs and movement execution costs in working memory (WM). The aim of the study was to clarify what kind of WM processes (verbal, spatial, or both) are recruited during movement planning and movement execution. Therefore, a WM task (verbal and spatial versions) was combined with a high-precision manual action. Participants initially planned a placing movement toward 1 of 2 targets, subsequently encoded verbal or spatial information in WM, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 117 publications
(183 reference statements)
11
52
0
Order By: Relevance
“…More generally, the interaction supports the notion of domain interactions in line with functional interactions of verbal working memory and grasping [101,102,103,104]. The present interaction shows that symbolic, conceptual information can be accessible for action specification together with motor commands and earlier than found in the Amsel et al study.…”
Section: Discussionsupporting
confidence: 88%
“…More generally, the interaction supports the notion of domain interactions in line with functional interactions of verbal working memory and grasping [101,102,103,104]. The present interaction shows that symbolic, conceptual information can be accessible for action specification together with motor commands and earlier than found in the Amsel et al study.…”
Section: Discussionsupporting
confidence: 88%
“…Given the emphasis on response speed in the present experiment, as well as the costs associated with movement replanning (Hughes, Seegelke, Spiegel et al, 2012;Spiegel, Koester, & Schack, 2013), participants may have maintained the original grasp posture plan, and tolerated less controllable final postures in order to mitigate the cognitive demands associated with grasp posture replanning. The observation that individuals are less likely to employ a cognitively demanding planning strategy (i.e., bimanual end-state comfort) when faced with an unexpected change in action goal suggests that individuals are concerned not only with comfortable end states, but also with computational efficiency during movement (re)planning.…”
Section: Perturbed Trialsmentioning
confidence: 98%
“…Finally, it has been recently found that a spatial manual task affects a spatial working memory task performance but not a verbal working memory task performance (Spiegel, Koester, & Schack, 2013).…”
Section: Downloaded By [University Of Cambridge] At 04:13 11 June 2016mentioning
confidence: 99%